Patients With the Malignant Profile Within 3 Hours of Symptom Onset Have Very Poor Outcomes After Intravenous Tissue-Type Plasminogen Activator Therapy - Inoue, Manabu (2012)
BACKGROUND AND PURPOSE: The malignant profile has been associated with poor outcomes after reperfusion in the 3- to 6-hour time window. The aim of this study was to estimate the incidence and prognostic implications of the malignant profile, as identified by CT perfusion, in intravenous tissue-type plasminogen activator-treated patients who were imaged <3 hours from stroke onset. METHODS: The incidence of the malignant profile, based on the previously published optimal perfusion-weighted imaging definition, was assessed in consecutive patients using a fully automated software program (RApid processing of Perfusion and Diffusion [RAPID]). A receiver operating characteristic curve analysis was done to identify time to maximum and core volume thresholds that optimally identify patients with poor outcome (modified Rankin Scale 5–6). RESULTS: Forty-two patients had an interpretable CT perfusion performed within 3 hours of symptom onset. Mean age was 74±14 years and median (interquartile range) National Institutes of Stroke Scale score was 13 (6–19). Four patients (9.5%) met the prespecified criteria for the malignant profile and all 4 had poor outcome. Receiver operating characteristic analysis determined that the best CT perfusion measure to identify patients with poor outcome was a cerebral blood flow based infarct core >53 mL (100% specificity and 67% sensitivity). This criterion identified 5 patients as malignant (12%). The poor outcome rate in these patients was 100% versus 7.1% in the 37 nonmalignant patients (P<0.001). CONCLUSION: The incidence of the malignant profile on CT perfusion is approximately 10% in tissue-type plasminogen activator-eligible patients imaged within 3 hours of symptom onset. The clinical outcome of these patients is very poor despite intravenous tissue-type plasminogen activator therapy.